Adapting and responding to a pandemic: Patient and family advisory councils in children's hospitals during COVID-19 - Pam Dardess; Deborah Dokken; Ndidi Unaka; Jesse Hsu; Mindy Hoang; Andrew Beck; Beverley Johnson (The Beryl Institute, 2022)
This mixed-methods study investigated the effects of the COVID-19 pandemic on Patient and Family Advisory Councils (PFACs) within children's hospitals in the United States. Specifically, the study sought to understand how PFACs adapted operations as a result of the COVID-19 pandemic, how patient and family advisors (PFAs) were engaged in the response to COVID-19, and the intersection of the COVID-19 pandemic with PFAC diversity, equity, and inclusion. The study consisted of a survey distributed to 228 children's hospitals, with a 73% response rate, and in-depth interviews with selected survey respondents (n=12). While COVID-19 temporarily disrupted PFAC operations and forced rapid adaptations, most children's hospital PFACs transitioned successfully to virtual meetings, with 86% reporting that their PFAC met at least once from March to December 2020 and 84% indicating that their PFAC planned to meet as frequently or more frequently than before the pandemic. The majority of respondents (72%) reported that attendance at virtual PFAC meetings was the same as or better than with in-person meetings. Interview participants reported benefits associated with virtual meetings, including the potential ability to recruit and engage PFAs who better reflected the diversity of the patients and families served by the hospitals. Children's hospitals are well-positioned to be leaders in the field, contributing to the development of new approaches, lessons learned, and best practices moving forward. This is especially true as hospitals continue to navigate the evolving realities of the COVID-19 pandemic, and as PFACs address challenges associated with maintaining diverse, equitable, and inclusive councils. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.